KONDISI TERUMBU KARANG DI PERAIRAN PANTAI MALALAYANG KOTA MANADO PROVINSI SULAWESI UTARA - Dannie R.S Oroh; Tommy M. Kontu; Oktavianus Lintong (JURNAL PESISIR DAN LAUT TROPIS, 2022)
Coral Reef data collection activities were carried out at Barracuda Station for the position and coordinates of the location of coral reef data collection. Field data collection activities were carried out on 29 June 2022. Data collection for the assessment of coral reef conditions was carried out using the Underwater Photo Transect (UPT) method. The UPT method is a method that utilizes technological developments, both digital camera technology and computer software technology. Data collection in the field is in the form of underwater photos which are taken by shooting using a Canon 16 underwater digital camera equipped with a compatible underwater housing. The photos from the shooting were then analyzed using CPCe computer software to obtain quantitative data. Barracuda Station is located in Malalayang Village. When the observations were made the weather was very good, not windy and not bumpy. The water conditions are very good with a visibility of approximately 20 meters and no current. Data collection was carried out at a depth of 4 meters on the reef flat. The bottom of the waters consists of dead coral with algae, live coral, and rubble. In general, the percentage of live coral cover observed at Barracuda station was 13.53% which puts the condition of coral reefs at Barracuda station in the "poor" category. At the Barracuda station, the percentage of Abiotic cover was 45.13% which was dominated by sandy substrate. Then the percentage of Dead Coral cover was found to be 32.80%, which was dominated by dead coral with algae and rubble. Keywords: Coral Reef, Barracuda Station, reef fish, Underwater photo transect ABSTRAK Kegiatan pengambilan data Terumbu Karang dilakukan di Stasiun Barracuda untuk posisi dan koordinat lokasi pengambilan data terumbu karang. Kegiatan Pengambilan data lapangan dilaksanakan pada tanggal 29 Juni 2022. Pengambilan data untuk penilaian kondisi terumbu karang dilakukan dengan menggunakan metode Underwater Photo Transect (UPT). Data di lapangan adalah berupa foto bawah air yang dilakukan dengan pemotretan menggunakan kamera digital bawah air Canon 16 dilengkapi dengan underwater housing yang komputibel. Foto-foto hasil pemotretan tersebut selanjutnya dianalisis menggunakan piranti lunak komputer CPCe untuk mendapatkan data- data yang kuantitatif. Stasiun Barracuda terletak pada Kelurahan Malalayang. Saat pengamatan dilakukan cuaca sangat baik, tidak berangin dan tidak bergelombang. Kondisi air sangat baik dengan jarak pandang kurang lebih 20 meter dan tidak berarus. Pengambilan data dilakukan pada kedalaman 4 meter di reef flat. Dasar perairan terdiri dari dead coral with algae, karang hidup, dan rubble. Secara umum persentase tutupan karang hidup yang teramati di stasiun Barracuda adalah 13,53% yang menempatkan kondisi terumbu karang di stasiun Barracuda dalam kateori “buruk”. Pada stasiun Barracuda mendapatkan nilai persentase tutupan Abiotik dengan nilai 45,13% yang di dominasi oleh substrat yang berpasir. Lalu persentase tutupan Dead Coral didapati dengan nilai 32,80%, yang di dominasi oleh dead coral with algae dan rubble. Kata Kunci : Terumbu Karang, Stasiun Barracuda, ikan karang, Underwater photo trans